2007
DOI: 10.1038/sj.ejcn.1602829
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour urinary thiamine as a biomarker for the assessment of thiamine intake

Abstract: Objective: To investigate 24-h urinary thiamine as a potential biomarker for thiamine intake for use in validation studies to assess the validity of dietary intake data collected by self-reporting dietary methods. Subjects: Seven male and six female healthy participants living for 30 days in a metabolic suite under strictly controlled conditions consuming their usual diet as assessed beforehand from four consecutive 7-day food diaries kept at home. During the 30-day study, all 24-h urine specimens were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
0
22
2
Order By: Relevance
“…To our knowledge, there is only a single report to assess CVWS and CVBS in urinary excretion of water-soluble vitamins (20 (20). In the present study, CVWS in urinary thiamin obtained was lower than the reported value.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…To our knowledge, there is only a single report to assess CVWS and CVBS in urinary excretion of water-soluble vitamins (20 (20). In the present study, CVWS in urinary thiamin obtained was lower than the reported value.…”
Section: Discussioncontrasting
confidence: 55%
“…Although we did not survey vitamin C intakes of the subjects in the few days prior to the experiment, the subjects might have taken less than 100 mg/ d of vitamin C prior to the experiment, and intake of 100 mg/d of vitamin C might have improved their values. Since higher vitamin C intake also increases urinary excretion of ascorbic acid (20,21,24), increase of urinary ascorbic acid during the experiment in female subjects might have been due to higher vitamin C intake during the experiment than in the previous days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a single study had investigated urinary vitamin as a possible marker for intake until 2007. Individuals' 30-day means of thiamin intake are highly correlated with their mean 24-hr urine thiamin levels under strictly controlled condition, showing 24-hr urinary thiamin as a useful marker for thiamin intake under strictly controlled conditions (Tasevska et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Methods using biomarkers for assessing vitamin intakes offer an effective approach to evaluate vitamin status in individuals. Many preceding studies have investigated urinary excretion as a biomarker for vitamin intake (1)(2)(3) . We have also reported recently that 24 h urinary levels of water-soluble vitamins correlate highly with their intakes for Japanese college students in a strictly controlled environment (4,5) .…”
mentioning
confidence: 99%